Mechanisms and recent advances in non-coding RNAs and RNA modifications in antiplatelet drug resistance - Ni, Ping; Chen, Kejie; Xiang, Jing; Shao, Haifeng; Chen, Xiaoling; Chen, Qiao; Wang, Lingling; Hao, Junli; Huang, Xinyi; Cao, Qing; Yang, Yali; Tan, Quandan; et al. (Frontiers in Genetics, 2025)
The high incidence and mortality rates of cardiovascular and cerebrovascular diseases make them a significant global health challenge. Antiplatelet drugs play a central role in the prevention and treatment of these diseases. Despite the wide range of available antiplatelet drugs, antiplatelet drug resistance is not rare. So optimizing drug use through personalized treatment strategies to achieve maximum therapeutic benefit remains a major challenge in clinical practice. Non-coding RNAs, including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs), have made significant progress in understanding their regulatory roles in drug resistance, becoming a frontier area of current research. In addition to the regulatory functions of non-coding RNAs, emerging studies have highlighted the role of RNA modifications, such as N6-methyladenosine (m6A), in the regulation of gene expression and cellular processes involved in antiplatelet drug resistance. These modifications contribute to the stability, splicing, and translation of RNA, further influencing their roles in drug resistance mechanisms. In recent years, significant progress has been made in the research of non-coding RNAs and RNA modifications, revealing their crucial roles in the mechanisms of antiplatelet drug resistance. This review focuses on the latest advancements in non-coding RNA research related to antiplatelet drug resistance and explores the emerging field of RNA modifications. It analyzes potential underlying mechanisms and discusses future research directions, aiming to provide new theoretical support and research perspectives for personalized precision antiplatelet.